2016
DOI: 10.1123/ijspp.2015-0542
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Haul Transmeridian Travel on Subjective Jet-Lag and Self-Reported Sleep and Upper Respiratory Symptoms in Professional Rugby League Players

Abstract: Results suggest that westward long-haul travel between Australia and the UK exacerbates subjective jet-lag and sleep responses, along with upper respiratory symptoms, in professional rugby league players. Of note, the increase in self-reported upper respiratory symptoms is a reminder that the demands of long-haul travel may be an additional concern in jet-lag for traveling athletes. However, due to the lack of sport-specific performance measures, it is still unclear whether international travel interferes with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 0 publications
0
39
0
Order By: Relevance
“…Overall, studies used a range of designs and methodological approaches. Three of the studies investigating long-haul travel reported a rating of jet lag in addition to sleep outcomes [41, 42, 58]. Time zone changes ranged from 1 to 11 h, with the maximum time zone change when travelling east being 8 h and the maximum when travelling west being 11 h. Across all studies, however, no change in sleep onset latency or sleep efficiency was reported following travel compared with pre-travel assessments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, studies used a range of designs and methodological approaches. Three of the studies investigating long-haul travel reported a rating of jet lag in addition to sleep outcomes [41, 42, 58]. Time zone changes ranged from 1 to 11 h, with the maximum time zone change when travelling east being 8 h and the maximum when travelling west being 11 h. Across all studies, however, no change in sleep onset latency or sleep efficiency was reported following travel compared with pre-travel assessments.…”
Section: Resultsmentioning
confidence: 99%
“…Time zone changes ranged from 1 to 11 h, with the maximum time zone change when travelling east being 8 h and the maximum when travelling west being 11 h. Across all studies, however, no change in sleep onset latency or sleep efficiency was reported following travel compared with pre-travel assessments. Changes in total sleep time and sleep quality reported were mixed, with one study showing a significant decrease in total sleep time following long-haul eastward travel [57] and another showing an increase following long-haul westward travel [42]. The majority of studies reported no change in sleep quality; however, Richmond et al [40] reported a significant decrease in sleep quality prior to away matches following a 2-h eastward time-zone change (mean score = 3.4), when compared with home matches (mean score = 3.8) in elite Australian Rules Football players.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This necessitates international travel not only for competition purposes, but also to attend training camps. Long-distance air travel across several time zones exposes passengers to travel fatigue and jet lag, which is suggested to negatively influence performance212–214 and susceptibility to illness 215 216. However, no link has yet been established for injuries.…”
Section: Load and Risk Of Injury In Athletesmentioning
confidence: 99%
“…31 Rather, long-haul or overnight travel is more likely to result in disrupted sleep behaviours and poorer sleep quantity and quality. 32 A limited number of studies investigating the effects of jet-lag in athletes indicates indirect effects on performance as a consequence of changes in mood and arousal that are concurrent to reduced sleep (for a review see Duffield & Fowler 28 ; Kölling et al 2 ). In terms of supporting recovery processes and enhancing an adaptation to the destination, behavioural strategies, such as arranging sleep-wake and meal times according to the target time, should be preferred over medications.…”
Section: Travel and Jet-lagmentioning
confidence: 99%